A Novel Approach to Find Author's Research Areas of Interests Using Graph Database - George, Soumya; Elayidom, M Sudheep; Santhanakrishnan, T (International journal of web portals, 2019)
Research areas of interests reveal the area of expertise of an author or the field in which the author has in-depth knowledge. This is one of the core components of an author profiles of any academic search engine that can be efficiently utilized by other authors or researchers to identify all authors who have proficiency in a specified field. This article proposes a graph-based approach for automatic creation of author profile by finding the author's area of interests in research using subject classification of their published papers. Classification accuracy of the author's research areas of interest also tested manually for 415 authors by comparing classified areas of interests of each author with areas of interests given in Google scholar profile. Total mismatch occurs only for 37 others. Results showed that accuracy could be improved by adding more papers.